Teachers’ perceptions of classroom climate and wellbeing: the role of physical classroom conditions in Chile - Muñoz-Troncoso, Flavio; Riquelme, Enrique H. (Frontiers in Psychology, 2025)
IntroductionClassroom climate has gained relevance as concerns have grown about its deterioration and its impact on both academic work and the daily lives of school communities. Different approaches have tried to explain this multivariate problem, yet few have considered the workspace itself as a factor that also explains the phenomenon. This study explores how physical classroom conditions influence perceived classroom climate among Chilean teachers, addressing a gap in research in the context of educational inequalities between public and private schools.MethodsWithin the framework of a quantitative, non-experimental and cross-sectional design, 6,038 teachers of different ages and genders participated. Scales from Chile’s JUNAEB program were adapted to measure classroom climate and personal well-being, both using a Likert-type response format.ResultsThe first-order model showed that the physical conditions of the classroom significantly and positively affect key latent variables, such as personal well-being (coefficient of 0.502) and teacher-student relationships (coefficient of 0.699). The model demonstrated good fit indices (X2 = 7,972.987, RMSEA = 0.061, CFI = 0.953), which supports the relevance of these relationships.DiscussionKey physical aspects such as space, lighting, and temperature were found to directly affect teachers’ perceptions of classroom climate, with implications for students’ emotional and academic outcomes. The study concludes by examining classroom infrastructure and resources as elements to consider when seeking to improve both personal well-being and classroom climate, ultimately fostering inclusive and effective learning environments.